2005
DOI: 10.1111/j.1365-2249.2005.02883.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic granulocytes are the predominant cell type infiltrating pancreatic islets in contact with ABO-compatible blood

Abstract: SummaryThe poor outcome of intraportal islet transplantation may be explained by the instant blood-mediated inflammatory reaction (IBMIR), characterized by islet entrapment in blood clots, leucocyte infiltration and disruption of islet morphology. Here we employ a newly developed in vitro system to identify the blood cells involved in this process. Islets were mixed with ABO-compatible blood in heparinized tubes and incubated for various times up to 6 h. Clots were analysed immunohistochemically for detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 34 publications
6
71
1
Order By: Relevance
“…Immunohistochemisty showed that islets were infiltrated by neutrophils ( Figure 1D), which was consistent with previous reports of a similar assay (18), and islets contained within the clots demonstrated widespread staining for C4d implicating complement-mediated cell lysis as a feature of IBMIR ( Figure 1G). …”
Section: Pvc Loop Perfusion Systemsupporting
confidence: 90%
“…Immunohistochemisty showed that islets were infiltrated by neutrophils ( Figure 1D), which was consistent with previous reports of a similar assay (18), and islets contained within the clots demonstrated widespread staining for C4d implicating complement-mediated cell lysis as a feature of IBMIR ( Figure 1G). …”
Section: Pvc Loop Perfusion Systemsupporting
confidence: 90%
“…Infusion of islet cells expressing TF into the portal vein tion (IBMIR) (2,19), which is characterized by coagulation and complement activation that leads to platelet triggers IBMIR, leading to the activation of coagulation pathway and the production of thrombin (16,24,29,31). consumption and neutrophil infiltration of the islets (25,37), and may even be stronger in the xenograft setCollectively, these data suggest the importance of TF expression by islets in regulating IBMIR. ting due to species barrier (4,33).…”
Section: Introductionmentioning
confidence: 83%
“…The identification of a targetable pathway able to prevent the recruitment of both these cells is an important finding. PMNs are the predominant cell type infiltrating the islets in experimental models (14), and a vicious cycle mediated by NKT and PMN IFN-γ-based cross-talk was recently demonstrated to be harmful to transplanted islets (15). Concordantly, NKT cell inhibition or deletion improves engraftment and delays islet rejection (1, 2, 15).…”
Section: Resultsmentioning
confidence: 99%